O professor de Cências : uma análise do impacto sociocultural no ensino fundamental - Rêgo, Greysi Dias (2018)
The present study wishes to present and discuss the difficulties that science teachers find in their different socio-cultural realities and environments. For that, historical aspects are evidenced, not only of the social and cultural areas, but also of the area of sciences, contemplated as discipline in the elementary school curriculum. Throughout the text, the questions that have built the current school in Brazil and the laws that govern it are worked on, in order to reveal and locate the subjects investigated. In addition, it is evident the curricular discussion, where the curriculum becomes an object of study and a fundamental part of the teaching exercise. The work presents, throughout the text, problems and discussions related to the different areas of knowledge that permeate the research, constructing them historically and tracing their connections. It then constructs a basis for an objective perspective and a view of the subject being researched, his perspective and an analysis of his discourse.